Effects of group therapy on female inmates’ self-belief and psychological well-being: a case study at Malaysian women prison - Khamsiah Ismail, Khamsiah; Nor Faridah Abd. Manaf, Nor Faridah; Farizah Jaafar, Farizah; Che Noraini Hashim, Che Noraini (2015)
There have been limited investigations on the factors that influence the development of psychological well-being in women in Malaysian prisons. Available literature indicates that several studies have been conducted to examine the benefits of intervention art therapy with prison inmates. These studies demonstrated a discernible improvement in mood, behaviour, and problem-solving, an increase in independence, a decrease in depressive symptoms, and also appropriate identity within the group dynamic. Other than that, art therapy facilitated disclosures of previously suppressed feelings, increased self-insight, and improved ability to deal with the stressful prison environment, and also helps to treat inmates who suffer from anxiety, depression. This preliminary study aimed to examine the impacts of group therapy on psychological well-being of women prisoners, particularly in Malaysia. Sixteen women inmates from Women Prison in Selangor, Malaysia were chosen and assigned by the prison authority to receive eight group therapy sessions. The respondents in this study were of different race/ethnic groups, different faiths, socio-economical and criminal backgrounds, aged between 27 to 56 years old. Self-report measures included the self-belief inventory which comprised of self-esteem, self-efficacy and spiritual well-being scales respectively, while psychological well-being indicated by decrease of stress, anxiety and depression levels. Due to limitation of access to the inmates, this preliminary study employs a pre-post test design study without a control group. Data was collected from participants’ level of performance before the intervention took place (pre-) and again was collected from the treatment group before and after completion of the therapy in duration of approximately three months. The inferences on the effect of the group therapy intervention will be examined by looking at the difference in the pre-test and post-test results. Statistical analyses employed for this study were descriptive statistics and paired-samples t-test. The results of this study revealed that there were significant differences in self-belief and psychological variables. The participants showed an increase level of self-efficacy and spiritual wellness and decrease level of depression as well as stress. Although not significant, their level of anxiety has also reduced Nevertheless the level of their self-esteem showed a slight decline. The findings of this study will be used to add knowledge on theory and to better understand the self-belief and psychological well-being of the inmates. The findings will also give some insights if group therapy can be considered as one of the programs that can support the rehabilitation process of the inmates